INTELLECTUAL MATURITY OF THE HUMAN RESOURCE AND ITS ROLE IN REDUCING JOB BURNOUT-AN ANALYTICAL STUDY OF THE OPINIONS OF A SAMPLE OF WORKERS IN AL-HAYAT AL-AHLIA HOSPITAL IN AL-NAJAF GOVERNORATE - Assist. Prof. Dr. Amer Abed Kareem Al-Thabhawee; Assist. Prof. Dr. Majid Jabbar Ghazai (Scholars Digest Publishing, 2024)
This research aims to know the relationship and impact between the intellectual maturity of the human resource through its dimensions (the ability to control oneself, personal conviction, gender) and job burnout through its dimensions (emotional exhaustion, inhumanity, low level of personal achievement). The research problem was identified in a main question: Is there a role for the intellectual maturity of the human resource in the researched organization to reduce job burnout in the work environment? The research used the questionnaire as a means to obtain data, where the research community was all employees of Al-Hayat Al-Ahly Hospital in Al-Najaf Governorate, and their number was (194) employees, and the research sample was (137) individuals, and (150) questionnaires were distributed, and the questionnaires retrieved and valid for statistical analysis were (137) A valid questionnaire for analysis. The data was analyzed using a set of statistical methods and the results were extracted using the computer program (SPSS v.22). The research reached a set of conclusions and recommendations, including that the organization, the research sample, strives towards building and supporting mature ideas, relying on talents and developing them in all hospital departments, and working to confront the biggest challenge that is represented in job burnout indicators in the organizational work environment, and working to confront them on objective grounds. Make the most of the advantages of human resource management in organizations.
Keywords: intellectual maturity of the human resource, job burnout, Al-Hayat National Hospital.